Blood cadmium as an indicator of dose in a long-term follow-up of workers previously exposed to cadmium - Järup, L; Persson, Bodil; Elinder, C-G (Scandinavian Journal of Work, Environment & Health, 1997)
' ' OBJECTIVES ': 'This investigation attempted to follow the tubular function of 46 workers initially examined in 1984 and heavily exposed to cadmium 1955 to 1978 and the occurrence of renal stones among these workers. The different markers of tubular dysfunction were also studied, and blood cadmium was evaluated as an estimate of dose after the cessation of cadmium exposure.' ' METHODS ': 'Cadmium in blood (B-Cd) and urine (U-Cd) and the urinary excretion of b2-microglobulin (U-b2-microglobulin), protein HC (a1-microglobulin) and N-Acetyl-b-D-glucosaminidase (NAG) were determined.' ' RESULTS ': 'Although cadmium exposure ceased in 1978, 40% of the workers showed signs of tubular dysfunction both in 1984 and in 1993. The current B-Cd was the best dose indicator. Dose-response relationships were found for B-Cd and various tubular markers (U-b2-microglobulin, protein HC and NAG). Protein HC appeared to be the most sensitive, as well as an early, indicator of cadmium-induced tubular dysfunction. The levels of U-Cd had an average decrease of 48% for persons with a normal tubular function, 56% for those with slight tubular dysfunction, and 62% for workers with severe tubular damage. A history of renal stones was significantly more common for workers with high B-Cd levels.' ' CONCLUSIONS ': 'Cadmium-induced tubular dysfunction is irreversible and best assessed in an analysis of protein HC (a1-microglobulin) in urine. B-Cd is the best dose estimate several years after the cessation of exposure, whereas U-Cd is less suitable for dose assessment in follow-up studies of persons with persistent tubular damage.
Keywords: alpha1-microglobulin; beta2-microglobulin; blood cadmium; N-acetyl-beta-D-glucosaminidase; protein alfa1-microglobulin; renal stones; tubular dysfunction